ANALISIS DAMPAK KEBERADAAN TOKO SWALAYAN TERHADAP OMZET PENJUALAN KIOS–KIOS KECIL DI KOTA MATARAM - Basri Basri (Master of Management, Mataram University, 2016)
The objective of the study was to evaluate the impact of stores existence toward sales turnover of stalls in Mataram city. Associative research design was adopted as the study guide. Purposive sampling techniques were used in which 100 copies of the research instrument were administered to stalls owner in Mataram city, out of which 100 copies of questionnaire were filled and returned. Test of validity and reliability, classical assumption test, and multiple linear regression analysis was used to analyse the data generated from respondents. The findings revealed that stores existence variable consisted of services, product diversification, price, and comfortable of consumer have significant influence on sales turnover of stalls at 0,05 level (2-tailed). The result of the research shows the variables negatively affecting sales turnover of stalls. Furthermore, price ranks the first follow by comfortable, product diversification, and services. This research will help the owner of stalls to understand and recognize the ranking of variables affecting sales turnover of stalls in Mataram city. Keywords: Stores Existence, Stall, and Sales Turnover.